Theo-anthropocentric Paradigm of Tafsir At-Tanwir by Muhammadiyah and its Application in the Interpretation of Surah Al-Baqarah/2: 286 - Basri, Muhammad Ridha; Nahar, Muhammad Hasnan; Bariqi, Sirajuddin (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This article examines the shift in meaning offered by Tafsir At-Tanwir by the Tarjih and Tajdid Council of PP Muhammadiyah towards surah al-Baqarah/2: 286. Tafsir At-Tanwir understands that the fragment of the verse lahā mā kasabat in that verse does not only mean recompense in the hereafter but also rewards in the world. Through the descriptive-analytical research method, the writer finds that the shift in meaning cannot be separated from the interpretation paradigm used by Tafsir At-Tanwir, namely the theo-anthropocentric paradigm. Theo-anthropocentric paradigm is a synthesis of the-centrism and anthropocentric paradigms. With this paradigm, Tafsir At-Tanwir carries the theory of corrective distributive justice as a form of correction to the theory of distributive justice proposed by John Rawls with the principle of proportional difference. The basic principle of this theory is that everyone gets rewarded according to their contribution. Tafsir At-Tanwir corrects this principle by stating that some people cannot possibly contribute due to special circumstances, such as physical disabilities or old age. For them, there is a wealth distribution mechanism with worldly and hereafter dimensions, such as through zakat, infaq, and alms. The development of the meaning of surah al-Baqarah/2: 286 is an implication of theo-anthropocentric paradigm.